Youth, work and philanthropic institutions - Neves, Delma Pessanha (Saúde e Sociedade, 2006)
Lack of employment and non-recognition of professional knowledge based on everyday experience and on the reflection of learning processes based on transfer through generations, have constrained parents and children in the elaboration of projects of inclusion of new generations through work. Institutional agents that could cooperate in this task cannot point alternatives, and, for this reason, almost always propose activities related to cultural or leisure practices, almost always temporary. Based on the analysis of three philanthropic institutions oriented towards education of youngsters from low income families, an analysis of some of the dilemmas faced by those actors is undertaken, suggesting facilitating perspectives for the making of proposals of youngster's inclusion in the work market.